Incorporation of herbs Serai Kayu (Eugenia polyantha) in noodles and its effect on the proximate composition, physical and sensory properties - Mustapha, Nurasyidah (2020)
Yellow noodles is known as one of staple food in Asia and yellow noodles consumption is expanding worldwide due to its low cost and convenience food product. Thus, yellow noodles production increases for the past few years in order to meet the consumer's demand. At present day, consumer would like to purchase functional foods which not only provide basic nutrition and also to promote health. Serai Kayu or known as Eugenia polyantha which contains the volatile compound compounds are potential antioxidants. Herbs are abundantly found but the utilization of herbs is limited. The aim of this study was to prepare a different percentage of Serai Kayu incorporated with yellow noodles and to investigate the different effects of incorporation of different percentages of Semi Kayu on proximate composition, texture, colour and sensory properties in yellow noodles. Serai Kayu were combined and incorporated in yellow noodles formulation at 5-20%. Yellow noodles prepared with no addition of Semi Kayu was served as control. Fresh Serai Kayu leave dried at 55° C and ground into powder form. All yellow noodles were subjected to proximate compositions according to AOAC standard method. The texture was analyzed by using texture analyzer while colour was analyzed by using chromameter. Sensory properties of noodles were evaluated using 9-point hedonic scale. From the results obtained, protein content was higher in yellow noodles containing reduced percentage of Serai Kayu than control while for fat, ash and moisture content, it was higher in noodles containing increased percentage of Serai Kayu. Yellow noodles incorporated with Serai Kayu show lower carbohydrate content than control. For colour analysis, the trend of L*, a* and b* for all noodles formulations were similar where when percentage of Serai Kayu increased, L*, a* and b* were lower compared to control. Hence, yellow noodles incorporated with 5% of Serai Kayu was the best formulations and was carried to sensory evaluation. Sensory evaluation indicated that incorporation 5% of Semi Kayu and control obtained same range of overall acceptance except for colour attributes, yellow noodles incorporated .5% of Semi Kayu has lower range compare to control. In conclusion, yellow noodles incorporated with 5% of Serai Kayu was the most acceptable in term of proximate composition colour and texture. Thus, it was highly suggested to be market.